Single-crystal positive electrode material for sodium-ion battery and preparation method and application of single-crystal positive electrode material

In the synthesis process of sodium ion battery positive electrode materials, the co-precipitation and molten salt method are used to optimize the morphology and element distribution of single crystals, which solves the problem of insufficient cyclic stability and rate performance of traditional materials, and achieves high performance and low cost The positive electrode material of sodium ion battery is suitable for commercial applications of sodium ion batteries.

CN119133409AActive Publication Date: 2024-12-13ANHUI XINNA MATERIAL SCIENCE & TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411317350.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode materials have shortcomings in terms of cycle stability, rate performance and cost. In particular, traditional layered oxide materials are difficult to accurately control the microstructure and element distribution during the synthesis process, resulting in large performance fluctuations and doping. The high proportion of hetero metal ions is difficult to synthesize.

Method used

By dissolving the nickel source and manganese source in water and carrying out co-precipitation reaction, a precursor powder is obtained, and then mixed with the sodium source, copper source and M compound for the first calcination, followed by a second calcination with the oxygen-containing compound, control The microstructure and elemental distribution of the material are optimized by the molten salt method, the sintering temperature is reduced, and the structural stability and electrochemical properties are improved through M element doping and oxygen compound coating.

Benefits of technology

The sodium ion battery single crystal cathode material that achieves high operating voltage, excellent cycling stability and rate performance is low-cost, suitable for industrial production, and exhibits excellent specific capacity and cycling performance in electrochemical tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133409A_ABST
    Figure CN119133409A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery single crystal positive electrode material and a preparation method and application thereof, and the material realizes high working voltage, excellent cycling stability and rate capability by accurately controlling chemical composition and microstructure. According to the preparation method, the problem that part of doped metal ions cannot be synthesized into the precursor through a coprecipitation method or synthesized into the precursor in a high proportion can be solved, the microstructure and element distribution uniformity of the material can be effectively controlled, and the performance is more excellent than that of a conventional multi-component oxide mechanical solid-phase synthesis method; the addition of the molten salt can optimize the single crystal morphology and reduce the sintering temperature, the doping of the M element can stabilize the structure and improve the air stability and the cycling stability under high voltage, and the coating of the oxygen-containing compound can reduce the side reaction of the positive electrode material and an electrolyte interface and the electrochemical performance under high voltage. The first-circle discharge specific capacity is 173.34 mAh / g, and the capacity retention ratio is still 91.5% after 100 times of cyclic charge and discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technology of preparing positive electrode materials, and in particular relates to a single crystal positive electrode material for a sodium ion battery and a preparation method and application thereof. Background Art

[0002] With the rapid growth of global demand for renewable energy and electric vehicles, the research and development of high-performance, low-cost energy storage materials has become particularly important. As a potential alternative technology, sodium-ion batteries have attracted widespread attention in recent years due to their abundant resources, low cost, and similar electrochemical properties to lithium-ion batteries. However, the commercialization of sodium-ion batteries still faces many challenges, among which the performance improvement of cathode materials is one of the keys.

[0003] At present, the cathode materials of sodium-ion batteries mainly include layered oxides, polyanion compounds and Prussian blue compounds. Among them, layered oxides are considered to be one of the most promising candidates for cathode materials due to their high theoretical capacity and good ion transport performance. However, existing layered oxide cathode materials often have problems such as poor cycle stability, insufficient rate performance, limited operating voltage and high cost, which limit their widespread application in sodium-ion batteries.

[0004] Specifically, the traditional layered oxide cathode materials are often synthesized by mechanical solid-phase synthesis. Although this method is simple and easy, it is difficult to accurately control the microstructure and element distribution of the material, resulting in large fluctuations in material performance. In addition, the synthesis of some doped metal ions in the coprecipitation method is difficult, and it is difficult to achieve high-proportion doping, which in turn affects the overall performance of the material.

[0005] In order to overcome the above technical difficulties, researchers are constantly exploring new synthesis methods and material modification strategies. Among them, the molten salt method has gradually become a research hotspot because it can optimize the single crystal morphology of the material, reduce the sintering temperature and reduce energy consumption. At the same time, through reasonable element doping and surface coating technology, the structural stability and electrochemical performance of the material can be further improved.

[0006] For example, the patent application with publication number CN114540934A discloses a method for preparing a single-crystal nickel-cobalt-manganese ternary positive electrode material. The preparation method comprises the following steps: S1: first prepare a single-crystal precursor; S2: dry-mix and granulate the single-crystal precursor and lithium compounds, doped metal compounds, additives, and deionized water using a stirring granulator, calcine in an oxygen atmosphere, and obtain a large-particle single-crystal ternary material after airflow crushing; S3: add lithium carbonate and aluminum nitrate to the obtained single-crystal ternary material and use the sol-gel method to wet-coat it in a reactor to form a uniform coating layer on the surface. S4: Calcinate in an air atmosphere to obtain a high-performance ternary positive electrode material. The preparation method provided by the invention is simple in process and easy in post-processing. The prepared material has excellent charge and discharge efficiency, discharge specific capacity, rate performance, and cycle performance.

[0007] And the patent application with publication number CN114695875A discloses a high-capacity single crystal ternary positive electrode material and its preparation method, wherein the positive electrode material is prepared by sintering a high nickel precursor, a lithium source and an additive containing the element M once, and then mixing with an additive containing the element A and sintering for a second time. The ternary positive electrode material described in the invention has a smaller particle size and a uniform particle size. The invention adopts a two-time sintering and doping method, which not only improves the structural stability of the positive electrode material, but also further improves its electrochemical performance, especially the discharge specific capacity and cycle stability. At the same time, the preparation method of the present invention is simple, low-cost, and conducive to industrial production.

[0008] However, in order to solve the performance bottleneck problem of traditional materials, improvements and innovations on existing sodium-ion battery positive electrode materials are also needed. Summary of the invention

[0009] In view of this, the present invention proposes a sodium ion battery single crystal positive electrode material and its preparation method and application. The material achieves high operating voltage, excellent cycle stability and rate performance by precisely controlling the chemical composition and microstructure, while reducing production costs, providing strong support for the commercial application of sodium ion batteries.

[0010] The specific technical solutions of the present invention are as follows:

[0011] The present invention provides a method for preparing a single crystal positive electrode material for a sodium ion battery, comprising the following steps:

[0012] (1) dissolving a nickel source and a manganese source in water respectively and mixing them to obtain a mixed salt solution;

[0013] (2) Add alkali solution to the mixed salt solution for coprecipitation reaction, and control the particle size of the precipitate to D 50 =5-6μm (in the embodiment of the present invention, D is selected 50=5 μm as an example), and drying after reaction to obtain precursor powder;

[0014] (3) mixing the precursor powder with the sodium source, the copper source, the titanium source, and the M compound, adding the molten salt, mixing evenly, and then performing a first calcination treatment to obtain a positive electrode material subjected to a first calcination treatment;

[0015] Wherein, the compound M is calcium carbonate, calcium oxide, barium carbonate, barium oxide, potassium carbonate or potassium oxide;

[0016] (4) treating the positive electrode material subjected to the first calcination treatment to obtain a single crystal positive electrode material subjected to the first calcination treatment, and uniformly mixing the single crystal positive electrode material subjected to the first calcination treatment with an oxygen-containing compound, and then subjecting the mixed material to a second calcination treatment to obtain the single crystal positive electrode material for a sodium ion battery.

[0017] Specifically, in step (1), the nickel source is nickel sulfate, nickel chloride, nickel nitrate or nickel acetate.

[0018] The manganese source is manganese sulfate, manganese chloride, manganese nitrate or manganese acetate;

[0019] The concentration of the mixed salt solution is 1.0-2.0 mol / L, and the molar ratio of the metal elements is 1:1.

[0020] In some embodiments of the present invention, in step (2), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the concentration of the alkali solution is 2.0-4.0 mol / L;

[0021] The coprecipitation temperature is 40-60°C,

[0022] The drying temperature is 90-120°C.

[0023] In some embodiments of the present invention, in step (3), the sodium source is sodium carbonate, sodium nitrate or sodium hydroxide.

[0024] The copper source is copper oxide, copper acetate, copper nitrate, copper oxalate, copper sulfate or copper chloride.

[0025] The titanium source is titanium dioxide, titanic acid, titanium tetrachloride or barium metatitanate.

[0026] The molten salt is sodium sulfate, sodium chloride or sodium phosphate;

[0027] The molar ratio of the metal element in the precursor powder to the sodium source in the sodium source is 1:0.9-1.1,

[0028] The molar ratio of the metal element to the copper source in the precursor powder is 16:1-2.

[0029] The molar ratio of the metal element to titanium in the precursor powder is 16:1-4.

[0030] The ratio of the metal element in the precursor powder to the metal element in the M compound is 1:0.01-0.03,

[0031] The molten salt doping amount is 0.5-2wt% of the precursor powder mass.

[0032] Preferably, in step (3), the conditions for the first calcination treatment are a calcination temperature of 800-1000° C. and a calcination time of 10-20 hours.

[0033] During mixing, a ball mill can be used for sufficient mixing, the rotation speed of the ball mill is 200-450 r / min, the mass ratio of balls to materials is 1:1-2:1, and the ball milling time is 3-5 h.

[0034] In some embodiments of the present invention, in step (4), the cathode material subjected to the first calcination treatment is subjected to air flow pulverization and sieving treatment to obtain a single crystal cathode material subjected to the first calcination treatment, wherein the sieving mesh number is 200-400 meshes.

[0035] In some embodiments of the present invention, in step (4), the oxygen-containing compound is boron oxide, boric acid, aluminum metaphosphate, tungsten oxide, zirconium oxide or titanium oxide; the coating amount of the oxygen-containing compound is 1000-3000 ppm of the sodium ion battery single crystal positive electrode material.

[0036] Preferably, in step (4), the second calcination treatment is carried out at a temperature of 400-600° C. and a calcination time of 5-15 hours.

[0037] During mixing, a ball mill can be used for uniform mixing, the rotation speed of the ball mill is 200-450r / r / min, the mass ratio of balls to materials is 1:1-2:1, and the ball milling time is 1-3h.

[0038] The present invention also provides a sodium ion battery single crystal positive electrode material prepared by the preparation method, the chemical formula of which is Na b M a Ni 0.5-x Cu x Mn 0.5-y Ti y O2 (0.96≤b≤1, 0.01≤a≤0.03, 0<x<0.5, 0<y<0.5).

[0039] The present invention also provides a sodium ion battery, comprising a positive electrode sheet, a separator and a negative electrode sheet, wherein the positive electrode sheet comprises the sodium ion battery single crystal positive electrode material.

[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0041] The present invention provides a high-performance sodium ion battery single crystal positive electrode material, the chemical formula of which is Na b M a Ni 0.5-x Cu x Mn 0.5-y Ti y O2 (0.96≤b≤1, 0.01≤a≤0.03, 0<x<0.5, 0<y<0.5). The positive electrode material provided by the present invention has high working voltage, good cycle stability, high rate performance and low cost, and is an ideal positive electrode material for sodium ion batteries. This method can solve the problem that some doped metal ions cannot be synthesized into the precursor by coprecipitation or synthesized into the precursor in a high proportion, and can effectively control the microstructure and uniform element distribution of the material, and the performance is better than the conventional multi-component oxide mechanical solid phase synthesis method. The addition of molten salt can optimize its single crystal morphology and reduce the sintering temperature (saving energy consumption). The structure can be stabilized by M element doping to improve its air stability and cycle stability under high voltage. N element (oxygen-containing compound) coating can reduce the side reactions at the interface between the positive electrode material and the electrolyte and the electrochemical performance under high voltage. The method of the invention is simple to operate, the raw materials are easily available, and it is suitable for industrial production. When it is used as a positive electrode material for sodium ion batteries in electrochemical tests, it shows excellent specific capacity and cycle performance.

[0042] At a current density of 0.1C (voltage window 2-4.3V), the first cycle discharge capacity is 173.34mAh / g. At a current density of 1C, after 100 cycles of charge and discharge, there is still a 91.5% capacity retention rate, showing excellent long cycle life and stability. This experimental method is simple, easy and low-cost, and can be expanded to be applied to the synthesis of other energy storage materials, thereby improving the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Ni obtained in Example 2 of the present invention 0.5 Mn 0.5 SEM image of (OH)2 precursor material;

[0044] Figure 2 This is a SEM image of the single crystal positive electrode material obtained in Comparative Example 2 of the present invention;

[0045] Figure 3 This is a SEM image of the single crystal positive electrode material obtained in Example 2 of the present invention;

[0046] Figure 4 This is a charge and discharge curve diagram of the single crystal positive electrode material obtained in Example 2 of the present invention;

[0047] Table 1 shows the first cycle discharge specific capacity of the example and comparative example samples at a current density of 0.1C and the capacity retention rate after 100 cycles at a current density of 1C. DETAILED DESCRIPTION

[0048] Example 1

[0049] Synthesis of precursor: A mixed salt solution of NiSO4.6H2O and MnSO4·H2O with a total concentration of 2.0 mol / L was pumped into a continuous stirred tank reactor. At the same time, a 2.5 mol / L NaOH solution was added to the reactor. The solution temperature was kept at 50°C during the entire coprecipitation process, and the precipitate particle size D was controlled. 50 =5μm. The precipitate was washed with deionized water and dried in air at 120°C to obtain Ni 0.5 Mn 0.5 (OH)2 precursor powder.

[0050] Synthesis of positive electrode materials: The dried Ni 0.5 Mn 0.5 (OH)2 powder was mixed with Na2CO3 at a molar ratio of M:Na=1:0.98 and with calcium carbonate at a molar ratio of M:Ca=1:0.01, with copper oxide and titanium dioxide at a molar ratio of 16:1, and sodium sulfate at a precursor mass of 0.25wt%, using a small ball mill (ball mill speed of 450r / min, ball-to-material mass ratio of 2:1, ball milling time of 3h), and then the mixture was calcined at 900°C in air at a heating rate of 5°C / min for 15h, and naturally cooled to room temperature to obtain the positive electrode material Na 0.98 Ca 0.01 Ni 0.45 Cu 0.05 Mn 0.45 Ti 0.05 O2-0.25%.

[0051] The calcined positive electrode material was subjected to air flow milling and passed through a 300-mesh vibrating screen. The sieved positive electrode material was ball milled with boron oxide according to its mass ratio of 1000 ppm (the ball mill speed was 300 r / min, the ball-to-material mass ratio was 1:1, and the ball milling time was 1 h), and then the mixture was calcined at 500 ° C in air at a heating rate of 5 ° C / min for 10 h, and naturally cooled to room temperature to obtain the positive electrode material NaNi 0.45 Cu 0.05 Mn 0.45 Ti 0.05 O2-0.25%@B2O3.

[0052] Example 2

[0053] Synthesis of precursors: A mixed salt solution of NiSO4·6H2O and MnSO4·H2O with a total concentration of 2.0 mol / L was pumped into a continuous stirred tank reactor. At the same time, a 2.5 mol / L NaOH solution was added to the reactor. The solution temperature was kept at 50°C during the entire coprecipitation process, and the precipitate particle size D was controlled. 50 =5μm. The precipitate was washed with deionized water and dried in air at 120°C to obtain Ni 0.5 Mn 0.5 (OH)2 precursor powder, SEM image as shown Figure 1 shown.

[0054] Synthesis of positive electrode materials: The dried Ni 0.5 Mn 0.5 (OH)2 powder and Na2CO3 according to the molar ratio of M:Na=1:0.96 and calcium carbonate according to the molar ratio of M:Ca=1:0.02, and copper oxide and titanium dioxide according to the molar ratio of 8:1, sodium sulfate according to the precursor mass 0.5wt%, using a small ball mill to fully mix (ball mill speed of 450r / min, ball-to-material mass ratio of 2:1, ball milling time of 3h), and then the mixture was calcined at 900℃ in air at a heating rate of 5℃ / min for 18h, and naturally cooled to room temperature to obtain the positive electrode material Na 0.96 Ca 0.02 Ni 0.4 Cu 0.1 Mn 0.4 Ti 0.1 O2-0.5%.

[0055] The calcined positive electrode material was subjected to air flow milling and passed through a 300-mesh vibrating screen. The sieved positive electrode material was mixed with boron oxide at a mass ratio of 1000 ppm by ball milling (the ball mill speed was 300 r / min, the ball-to-material mass ratio was 1:1, and the ball milling time was 1 h). The mixture was then calcined at 500 °C in air at a heating rate of 5 °C / min for 10 h and naturally cooled to room temperature to obtain the positive electrode material Na 0.96 Ca 0.02 Ni 0.4 Cu 0.1 Mn 0.4 Ti 0.1 O2-0.5%@B2O3, SEM picture as shown Figure 3 shown.

[0056] Example 3

[0057] Synthesis of precursors: A mixed salt solution of NiSO4.6H2O and MnSO4·H2O with a total concentration of 3.0 mol / L was pumped into a continuous stirred tank reactor. At the same time, a 3.0 mol / L NaOH solution was added to the reactor. The solution temperature was kept at 50°C during the entire coprecipitation process, and the precipitate particle size D was controlled. 50 =5μm. The precipitate was washed with deionized water and dried in air at 120°C to obtain Ni 0.5 Mn 0.5 (OH)2 precursor powder.

[0058] Synthesis of positive electrode materials: The dried Ni 0.5 Mn 0.5 (OH)2 powder was mixed with Na2CO3 at a molar ratio of M:Na=1:0.96 and with calcium carbonate at a molar ratio of M:Ca=1:0.02, with copper oxide and titanium dioxide at a metal element molar ratio of 16:1 and 4:1, respectively, and sodium sulfate at 1.0wt% of the precursor mass, using a small ball mill (the ball mill speed was 450r / min, the ball-to-material mass ratio was 2:1, and the ball milling time was 3h), and then the mixture was calcined at 900°C in air at a heating rate of 5°C / min for 18h, and naturally cooled to room temperature to obtain the positive electrode material Na 0.96 Ca 0.02 Ni 0.45 Cu 0.05 Mn 0.2 Ti 0.2 O2-1.0%.

[0059] The calcined positive electrode material was subjected to air flow milling and passed through a 300-mesh vibrating screen. The sieved positive electrode material was mixed with boron oxide at a mass ratio of 1000 ppm by ball milling (the ball mill speed was 400 r / min, the ball-to-material mass ratio was 1:1, and the ball milling time was 1 h). The mixture was then calcined at 550°C in air at a heating rate of 5°C / min for 10 h and naturally cooled to room temperature to obtain the positive electrode material Na 0.96 Ca 0.02 Ni 0.45 Cu 0.05 Mn 0.2 Ti 0.2 O2-1.0%@B2O3.

[0060] Comparative Example 1

[0061] Synthesis of precursor: A mixed salt solution of NiSO4.6H2O and MnSO4·H2O with a total concentration of 2.0 mol / L was pumped into a continuous stirred tank reactor. At the same time, a 2.0 mol / L NaOH solution was added to the reactor. The solution temperature was kept at 50°C during the entire coprecipitation process, and the precipitate particle size D was controlled.50 =5μm. The precipitate was washed with deionized water and dried in air at 100°C to obtain Ni 0.5 Mn 0.5 (OH)2 precursor powder.

[0062] Synthesis of positive electrode materials: The dried Ni 0.5 Mn 0.5 (OH)2 powder and Na2CO3 were mixed in a small ball mill at a molar ratio of 2:1, and then the mixture was calcined at 900°C in air at a heating rate of 5°C / min for 15 h and naturally cooled to room temperature to obtain the positive electrode material NaNi 0.5 Mn 0.5 O2.

[0063] Comparative Example 2

[0064] Solid phase synthesis of positive electrode materials: According to Na 0.96 Ca 0.02 Ni 0.4 Cu 0.1 Mn 0.4 Ti 0.1 The molar ratio of metal elements in the O2 positive electrode material is as follows: nickel oxide, copper oxide, manganese oxide, titanium dioxide, sodium carbonate and calcium carbonate are weighed and fully mixed using a small ball mill (mill speed is 450r / min, ball-to-material mass ratio is 2:1, and ball milling time is 5h). Then the mixture is calcined at 900℃ in air at a heating rate of 5℃ / min for 18h and naturally cooled to room temperature to obtain the positive electrode material Na 0.96 Ca 0.02 Ni 0.4 Cu 0.1 Mn 0.4 Ti 0.1 O2.

[0065] The calcined positive electrode material was subjected to air flow milling and passed through a 200-mesh vibrating screen. The sieved positive electrode material was mixed with boron oxide at a mass ratio of 1000 ppm by ball milling (the ball mill speed was 400 r / min, the ball-to-material mass ratio was 1:1, and the ball milling time was 1 h). The mixture was then calcined at 550°C in air at a heating rate of 5°C / min for 10 h and naturally cooled to room temperature to obtain the positive electrode material Na 0.96 Ca 0.02 Ni 0.4 Cu 0.1 Mn 0.4 Ti 0.1 O2@B2O3, SEM picture Figure 2 shown.

[0066] Test Example 1

[0067] Preparation of battery pole pieces: Active material, conductive agent (SP), and binder (PVDF) are weighed in a mass ratio of 90:5:5. First, 45 mg of the weighed active material is dissolved in a certain amount of NMP solvent, and stirred continuously until the active material is completely dissolved; then PVDF is added to the active material solution; after PVDF and active material are mixed, the conductive agent is added, and then stirred continuously. After the active material, SP and PVDF are mixed, the slurry is evenly applied to the aluminum foil using a coater, and the copper foil coated with the slurry is transferred to a vacuum drying oven at 120°C for drying for 12 hours; finally, the dried electrode sheet is cut into a circular electrode sheet with a diameter of 14 mm using a cutting machine, and the cut electrode sheet is weighed.

[0068] Assembly of CR2032 button cell: In a glove box under argon atmosphere, stack the positive electrode shell, negative electrode sheet, electrolyte, diaphragm, electrolyte, metal sodium sheet, gasket, shrapnel, and negative electrode shell in this order, and then press them into button cells using a sealing machine, and test them after 12 hours of activation. The electrolyte is 1M NaPF6 / (PC+5%FEC); the diaphragm uses Whatman glass fiber, and the battery test voltage window is set to 2-4.3V.

[0069] The test results are shown in Table 1.

[0070] Table 1

[0071]

[0072] From Table 1 and Figure 4 The results show that the 0.1C first-cycle discharge capacity and 100-cycle retention rate of the single crystal positive electrode material obtained by conventional dry mixing in Examples 1 and 2 using this method are significantly improved. After using this method and doping and coating, the first-cycle discharge capacity of Example 2 at a voltage of 2-4.3V reaches a maximum of 173.34mAh / g, and the retention rate after 100 cycles at 1C is 91.5%.

Claims

1. A method for preparing a single crystal positive electrode material for a sodium ion battery, characterized in that: The following steps are involved: (1) dissolving a nickel source and a manganese source in water respectively and mixing them to obtain a mixed salt solution; (2) Add alkali solution to the mixed salt solution for coprecipitation reaction, and control the particle size of the precipitate to D 50 =5-6μm, and the precursor powder is obtained by drying after the reaction; (3) mixing the precursor powder with the sodium source, the copper source, the titanium source, and the M compound, adding the molten salt, mixing evenly, and then performing a first calcination treatment to obtain a positive electrode material subjected to a first calcination treatment; Wherein, the compound M is calcium carbonate, calcium oxide, barium carbonate, barium oxide, potassium carbonate or potassium oxide; (4) treating the positive electrode material subjected to the first calcination treatment to obtain a single crystal positive electrode material subjected to the first calcination treatment, and uniformly mixing the single crystal positive electrode material subjected to the first calcination treatment with an oxygen-containing compound, and then subjecting the mixed material to a second calcination treatment to obtain the single crystal positive electrode material for a sodium ion battery.

2. The method for preparing a single crystal positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step (1), the nickel source is nickel sulfate, nickel chloride, nickel nitrate or nickel acetate, The manganese source is manganese sulfate, manganese chloride, manganese nitrate or manganese acetate; The concentration of the mixed salt solution is 1.0-2.0 mol / L, and the molar ratio of the metal elements is 1:

1.

3. The method for preparing a single crystal positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step (2), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the concentration of the alkali solution is 2.0-4.0 mol / L; The coprecipitation temperature is 40-60°C, The drying temperature is 90-120°C.

4. The method for preparing a single crystal positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step (3), the sodium source is sodium carbonate, sodium nitrate or sodium hydroxide, The copper source is copper oxide, copper acetate, copper nitrate, copper oxalate, copper sulfate or copper chloride. The titanium source is titanium dioxide, titanic acid, titanium tetrachloride or barium metatitanate. The molten salt is sodium sulfate, sodium chloride or sodium phosphate; The molar ratio of the metal element in the precursor powder to the sodium source in the sodium source is 1:0.9-1.1, The molar ratio of the metal element to the copper source in the precursor powder is 16:1-2. The molar ratio of the metal element to titanium in the precursor powder is 16:1-4. The ratio of the metal element in the precursor powder to the metal element in the M compound is 1:0.01-0.03, The molten salt doping amount is 0.5-2wt% of the precursor powder mass.

5. The method for preparing a single crystal positive electrode material for a sodium ion battery according to claim 4, characterized in that: In step (3), the conditions of the first calcination treatment are a calcination temperature of 800-1000° C. and a calcination time of 10-20 hours.

6. The method for preparing a single crystal positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step (4), the positive electrode material subjected to the first calcination treatment is subjected to air flow pulverization and sieving treatment to obtain a single crystal positive electrode material subjected to the first calcination treatment, wherein the sieving mesh number is 200-400 meshes.

7. The method for preparing a single crystal positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step (4), the oxygen-containing compound is boron oxide, boric acid, aluminum metaphosphate, tungsten oxide, zirconium oxide or titanium oxide; the coating amount of the oxygen-containing compound is 1000-3000ppm of the sodium ion battery single crystal positive electrode material.

8. The method for preparing a single crystal positive electrode material for a sodium ion battery according to claim 7, characterized in that: In step (4), the conditions for the second calcination treatment are a calcination temperature of 400-600° C. and a calcination time of 5-15 hours.

9. A sodium ion battery single crystal positive electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. A sodium ion battery, comprising a positive electrode sheet, a separator and a negative electrode sheet, characterized in that: The positive electrode sheet comprises the sodium ion battery single crystal positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method of single-crystal nickel-cobalt-manganese ternary positive electrode material

    CN114540934A

  • High-capacity single-crystal ternary positive electrode material and preparation method thereof

    CN114695875A

  • Method for preparing Cu and Zn-doped layered oxide sodium-ion battery positive electrode material with assistance of precursor and application of Cu and Zn-doped layered oxide sodium-ion battery positive electrode material

    CN114715953A

  • Monocrystalline sodium ion battery positive electrode material and preparation method and application thereof

    CN115275134A

  • O3 type sodium ion positive electrode material, preparation method thereof and sodium ion battery

    CN116495799A

Cited By

  • Method for preparing high-capacity and long-cycle sodium electric single-crystal positive electrode material under assistance of carbonate

    CN120250133A